Whose kingdom is it anyway?: the sons of Zebedee as antitypes for Adonijah in Matthew 20 - Rudman, Dominic (Biblische Notizen, 2005)
Mk 10,35-40, which relates how the Boanerges approached Jesus in the hope of obtaining a special position when he came into his own, has been subject to several changes in Mt 20,20-23, notably in Matthew’s presentation of the request being made by the mother of James and John. This article argues that the introduction of the mother, and of several more minor changes, is the product of the Matthean author’s desire to draw a parallel between the present text and 1 Kings 2, in which Adonijah, like the Boanerges, seeks to obtain an inappropriate position in a Davidide’s kingdom. In doing so, the Matthean author invites his readership to reflect theologically on the motives of the Boanerges and on the nature of Jesus’ kingship.